Le Quodlibet I, question 17 de Jacques de Viterbe: introductIon, traduction et notes - Côté, Antoine (Université d'Ottawa | University of Ottawa, 2012)
This article provides a historical and doctrinal introduction to, and annotated translation of, James of Viterbo’s Quodlibet I, 17, in which James asks whether or not the pope has the right to absolve usurers. The article argues that the principal interest of the Quodlibet lies in the philosophical justification it provides for the pope’s supremacy in temporal matters. It also examines the relation between the Quodlibet and the later De regimine Christiano and points to a slight shift in James’ position towards greater moderation
Keywords: papacy; seculars; spirituals; James of Viterbo